2018
DOI: 10.21037/sci.2018.11.01
|View full text |Cite
|
Sign up to set email alerts
|

Stem cell therapy for patients with diabetes: a systematic review and meta-analysis of metabolomics-based risks and benefits

Abstract: Background: There is a general agreement that to ensure promising results of stem cell therapy in patients with diabetes, one must first understand its risks and benefits; thus, if the risk is sufficiently low along with many benefits, it can lead to developing a novel therapeutic approach based on sound science.Methods: A systematic review and meta-analysis was performed using all available clinical trials to determine the benefits and risks associated with stem cell therapy in patients with diabetes (both T1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
22
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 42 publications
2
22
0
1
Order By: Relevance
“…Study Alzheimer's disease Genetically or pharmacologically upregulating growth factors like brain-derived neurotrophic factor, IGF-1, nerve growth factor, and vascular endothelial growth factor that induce neurogenesis (25). (6,(35)(36)(37)(38)(39). Cardiovascular diseases are a major area of concern as they have a high incident, morbidity and mortality rate and include a variety of chronic conditions such as myocardial infarction (MI), atherosclerosis and aneurysms.…”
Section: Neural Precursor Cell Transplantation Effects On Myelinationmentioning
confidence: 99%
See 1 more Smart Citation
“…Study Alzheimer's disease Genetically or pharmacologically upregulating growth factors like brain-derived neurotrophic factor, IGF-1, nerve growth factor, and vascular endothelial growth factor that induce neurogenesis (25). (6,(35)(36)(37)(38)(39). Cardiovascular diseases are a major area of concern as they have a high incident, morbidity and mortality rate and include a variety of chronic conditions such as myocardial infarction (MI), atherosclerosis and aneurysms.…”
Section: Neural Precursor Cell Transplantation Effects On Myelinationmentioning
confidence: 99%
“…Stem cell therapy has also been studied in treating cancers, obesity, Parkinson's disease, hearing recovery, Alzheimer's disease, etc. ( 6 , 35 – 39 ). Cardiovascular diseases are a major area of concern as they have a high incident, morbidity and mortality rate and include a variety of chronic conditions such as myocardial infarction (MI), atherosclerosis and aneurysms.…”
Section: Personalized Regenerative Medicinementioning
confidence: 99%
“…Cancer stem cells (CSCs) are immortal cells within a tumor that can self-renew and give rise to the bulk cancer cells [1,2]. Tumors with more CSCs are phenotypically more malignant and more likely to establish resistance to many treatment modalities [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…However, it is unclear which type of stem cells is most effective in treating diabetes, and one study reported that severe infectious diseases occur after stem cell treatment [18]. Two meta-analyses explored the effects of stem cells on diabetes, but their findings were inconsistent [19,20]. Indeed, Rahim et al showed that stem cell therapy has a negative effect on C-peptide in patients with type 2 diabetes [19], but El-Badawy et al found that stem cell therapy can improve C-peptide levels [20].…”
mentioning
confidence: 99%
“…Two meta-analyses explored the effects of stem cells on diabetes, but their findings were inconsistent [19,20]. Indeed, Rahim et al showed that stem cell therapy has a negative effect on C-peptide in patients with type 2 diabetes [19], but El-Badawy et al found that stem cell therapy can improve C-peptide levels [20]. In addition, they studied changes in glycosylated hemoglobin (HbA1c) and C-peptide but did not systematically analyze fasting plasma glucose (FPG) levels, insulin requirements, or adverse events after stem cell therapy.…”
mentioning
confidence: 99%